An image-based geometric model for numerical simulation of blood perfusion within the liver lobules. Issue 13 (2nd October 2020) - Ahmadi-Badejani, R.; Mosharaf-Dehkordi, M.; Ahmadikia, H.
Abstract: An image-based numerical algorithm is presented for simulating blood flow through the liver tissue. First, a geometric model is constructed by applying image processing techniques on a real microscopic image of a liver tissue. Then, incompressible blood flow through liver lobules is simulated. Effects of tissue heterogeneity and deformity, presence/absence of the second central vein in a particular lobule, and apparent sinusoids density in the liver cross section on the blood flow are investigated. Numerical results indicate that the existence of thick low permeability vascular septum, high permeability sinusoids, and lobule tissue heterogeneity can considerably affect interlobular and intralobular blood flow. Graphical Abstract: